Tea Tree Oil Improves Energy Metabolism, Non-Specific Immunity, and Microbiota Diversity via the Intestine-Hepatopancreas Axis in Macrobrachium rosenbergii under Low Fish Meal Diet Administration - Mingyang Liu; Xiaodi Xu; Cunxin Sun; Xiaochuan Zheng; Qunlan Zhou; Changyou Song; Pao Xu; Qiang Gao; Bo Liu (MDPI AG, 2023)
Tea tree oil (TTO) is an essential plant oil with diverse antibacterial and antioxidant properties; however, whether the role played by TTO in low fish meal (LF) diets induced the observed effects in the farmed crustaceans remains unclear. Therefore, this study used Macrobrachium rosenbergii as the model crustacean, and an 8-week feeding experiment with NF (normal fish meal), LF (soybean meal replacing 40% fish meal), and LFT (LF with 200 mg/kg TTO) diets was conducted to evaluate the positive effects of TTO under the LF diet. Compared to the NF diet, the LF diet reduced hemolymph antioxidant capacity and non-specific immunity, and induced hepatopancreas apoptosis and damage. However, in comparison with LF, LTF significantly ameliorated morphological impairment in the hepatopancreas, improved hepatopancreas energy metabolism by upregulating the Bcl-2/Bax and Akt/mTOR pathways, and enhanced antioxidant and non-specific immune capacity by activating the NF-κB/NO pathway. In addition, LFT repaired intestinal barrier injury and the imbalance of intestinal microbiota induced by the LF diet. Moreover, the Pearson correlation revealed the variations of the above indicators, which were related to the abundance changes of Klebsiella, Clostridium sensu stricto 12, Thermobifida, Bifidobacterium, and Alistipes, indicating that these microbes might serve as prospective targets for the intestine-hepatopancreas axis to affect hepatopancreas apoptosis, metabolism, and non-specific immunity. In summary, 200 mg/kg TTO supplementation mediated gut microbiota and positively improved energy metabolism and non-specific immunity, thereby alleviating hepatopancreas dysplasia and damage induced by the LF diet in M. rosenbergii.